2005
DOI: 10.1037/0022-006x.73.6.1181
|View full text |Cite
|
Sign up to set email alerts
|

Intervention outcomes for girls referred from juvenile justice: Effects on delinquency.

Abstract: An increasing number of girls are entering the juvenile justice system. However, intervention programs for delinquent girls have not been examined empirically. We examined the 12-month outcomes of a randomized intervention trial for girls with chronic delinquency (N = 81). Girls were randomly assigned into an experimental condition (Multidimensional Treatment Foster Care [MTFC]) or a control condition (group care [GC]). ANCOVAs indicated that MTFC youth had a significantly greater reduction in the number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
121
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 9 publications
(14 reference statements)
6
121
0
Order By: Relevance
“…Multidimensional Treatment Foster Care (MTFC) In studies comparing youth randomized into either MTFC or diverse group care programs, Chamberlain and colleagues found that MTFC youth spent less time in locked settings, had fewer criminal referrals (Chamberlain, & Reid, 1998;Leve, Chamberlain & Reid, 2005) and had fewer delinquent peers at follow-up . Males in MTFC were more likely to complete treatment and return home to family compared to males in group care (Chamberlain & Reid, 1998).…”
Section: Evidence For Treatment Foster Care's Effectivenessmentioning
confidence: 99%
“…Multidimensional Treatment Foster Care (MTFC) In studies comparing youth randomized into either MTFC or diverse group care programs, Chamberlain and colleagues found that MTFC youth spent less time in locked settings, had fewer criminal referrals (Chamberlain, & Reid, 1998;Leve, Chamberlain & Reid, 2005) and had fewer delinquent peers at follow-up . Males in MTFC were more likely to complete treatment and return home to family compared to males in group care (Chamberlain & Reid, 1998).…”
Section: Evidence For Treatment Foster Care's Effectivenessmentioning
confidence: 99%
“…They and other researchers (e.g., Courtney, 2000) have called for experimental research to improve practices in the child welfare system (CWS), particularly for children in out-of-home care. In this study, we tested Correspondence should be directed to Patricia Chamberlain, Oregon Social Learning Center, 10 Shelton McMurphey Boulevard, Eugene, (541) 485-2711; fax, (541) NIH-PA Author Manuscript NIH-PA Author Manuscript NIH-PA Author Manuscript the effectiveness of an intervention designed to strengthen foster parents' parenting skills through the implementation of a theoretically-based intervention that had been shown in previous randomized studies to have positive short-and long-term effects on child outcomes Chamberlain & Reid, 1991;Leve et al, 2005). The intervention was expected to lead to improvements in foster parent child management skills, which were expected to result in fewer child behavior problems.…”
Section: Abstract Parent Management Training; Foster Parents; Effectimentioning
confidence: 99%
“…Multidimensional Treatment Foster Care (MTFC) has been used with foster care providers to provide treatment to adolescents referred by juvenile justice as an alternative to placement in group or residential care (Chamberlain, & Reid, 1998;Leve et al, 2005). MTFC has been adapted for use with children with severe mental health disorders who are being discharged from inpatient psychiatric care (Chamberlain & Reid 1991) and with high-risk preschoolers in foster care (Fisher et al, 2005).…”
Section: Abstract Parent Management Training; Foster Parents; Effectimentioning
confidence: 99%
See 2 more Smart Citations